Reverse logistics and environmental sustainability in selected manufacturing entities in Kampala district, Uganda - Rugasira, Jack; Agaba, Moses; Byarugaba, Jotham Mbiito; Asiimwe, Jane (Kabale University Interdisciplinary Research Journal, 2022)
The purpose of this study was to empirically establish the relationship between reverse logistics and environmental sustainability in Uganda, focusing on selected manufacturing entities in the Kampala district. The study employed a cross-sectional design. The study also used quantitative approaches in collecting and analysing the data both descriptively and inferentially. The study population was 675 manufacturing entities. Using the purposive sampling technique, the study took a sample of 248. Data were obtained from 186 usable questionnaires. The researcher applied Statistical Package for Social Scientists (SPSS) to test all four hypotheses. The results are presented in terms of descriptive statistics and inferential statistics in terms of correlation analysis, simple regression and multiple regression analysis models. Results indicate that Pearson’s correlation results indicate a relatively moderate, positive and significant association between Green manufacturing and Environmental Sustainability in Kampala industries. The findings show that there was a low but positive correlation (r= 0.480, sig .000, p< .01) between Reverse Logistics and Environmental Sustainability. This implies that any improvements made in reverse logistics can be associated positively with environmental sustainability in Kampala. The study, therefore, concludes that findings are partially supportive of The National Environment Act, 2019; specifically concerning the prohibition of littering, Trans boundary movement of waste and classification and management of hazardous waste. It is therefore recommended that National Environment Management Authority and Uganda revenue Authority work out a rewards system for firms that actively practice Reverse Logistics as this undercuts pollution as reduces waste dumped in water bodies and the environment.